Analisis Capaian Pembelajaran Pada Mahasiswa Akuntansi (Eksperimen Kuasi) - Nicko Kornelius Putra; Agus Kuntoro (Akademi Akuntansi YKPN Yogyakarta, 2020)
Abstract. This study aims to analyze the learning outcomes shown by accounting students in certain subjects. The effort to realize learning outcomes is carried out through course simulation learning tools in the form of quizzes that are packaged in the games